Campania: Territory and City in Front of the Challenge of the Logistics - Mazzeo, Giuseppe (TeMA - Journal of Land Use, Mobility and Environment, 2010)
Logistics can be defined as the process of planning, organization and control of all the activities of transport and storage of goods and informations; it interests all the productive phases, from the acquisition of raw materials, to the production process in the factories, up to the delivery of the finished products to the final customers. The specific trend of the production’s process due to the logistics involves the flows and the storage of goods, from raw materials to semi-finished goods to finished products, so they are available to consumers. In this way the logistics intersects the territory at different stages of its activity: when the raw materials are brought to the factory, when the factory sends to other factories semi-production units, where products are stored in equipped areas, and when the final goods are brought to terminal sales. Within the Southern territorial system the Campania is an important hub in the transport and sorting of goods. This role has made stronger after the carrying out of new infrastructures dedicated to the logistics, related to other support infrastructures, as railways and motorways. The regional system presents nationwide excellence’s peaks that could encourage its role in this sector, but there are also negative factors that may to slow the take-off of the sector. The reference is to the infrastructures and operating bottlenecks interfering the efficiency, but also to the weakness of the regional production’s system that doesn’t ensures a local critical mass to the logistics of the region. A third aspect is the lack of a clear structure of programming investment and greater clarity of roles assigned to various initiatives, arising mainly on local, uncoordinated pushes. The paper analyzes the situation of territorial logistics and of its spatial interrelationship in Campania, identifying strengths, weaknesses, and potential evolutionary factors. The discussion faces up aspects of territorial logistics; they differ from the urban logistics for the amount of handled commodities and for the concentration in a few strategic poles, because these logistics platforms require specialized equipments and wide spaces for movement and deposit. The first part of the paper analyses the relationships between territory and logistics and identifies either the main elements of interconnection or, often, of crisis in the use of physical space, for reasons of the diverging objectives between the territorial government and the economic actors. The second part considers the condition of good’s movement in relation to the Mediterranean port facilities, to the state of the logistics system of Campania, and to the economic and territorial situation of the region. To this purpose, the paper also explores the evolution of territorial planning in Campania, highlighting how a series of choices, including those related to the location of logistics facilities, have been made outside of existing planning tools.